1997
DOI: 10.1007/s007050050121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ovine herpesvirus-2 infection in sheep

Abstract: A polymerase chain reaction test for the detection of ovine herpesvirus-2 (OHV-2) DNA was used to identify sites of OHV-2 infection in peri-natal lambs and in adult sheep. OHV-2 was detected in the nasal secretions from all lambs within a period of two months following birth. Subsequently, OHV-2 DNA was identified in a number of epithelial tissues including the cornea, turbinates and pharynx. In addition, OHV-2 DNA was detected exclusively in B-lymphocytes from six of ten adult sheep tested. An infection cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
0
26
1
2
Order By: Relevance
“…Without causing clinically significant damage to its carrier host, the virus reactivates from the latent to the lytic mode, during which infectious virus is produced and transmitted to maintain viral reservoirs and to induce disease in other species. Lymphocytes are host cells for OvHV-2 in sheep, although which subsets are infected has not been clearly defined (2,10). Little is known about the nature of the virus-carrier host relationship, such as the sites of productive viral infection.…”
mentioning
confidence: 99%
“…Without causing clinically significant damage to its carrier host, the virus reactivates from the latent to the lytic mode, during which infectious virus is produced and transmitted to maintain viral reservoirs and to induce disease in other species. Lymphocytes are host cells for OvHV-2 in sheep, although which subsets are infected has not been clearly defined (2,10). Little is known about the nature of the virus-carrier host relationship, such as the sites of productive viral infection.…”
mentioning
confidence: 99%
“…Though we did not attempt other transmission routes in this study, there have been several reports that no OvHV-2 DNA was detected in the urinary bladder [2], urine or faeces [7,8]. Consequently, it is suggested that nasal secretions play an active role in transmission of the virus among sheep.…”
Section: Discussionmentioning
confidence: 85%
“…Li et al [12] reported that lambs could be raised free of the virus when they were separated from the flock at 2.5 months of age. On the other hand, Baxter et al [2] reported that lambs were infected at very young ages of under 2 months. In our unpublished data, most lambs in a flock became infected with OvHV-2 between 2 and 6 months after birth; however, all the lambs born in the flock the next year were infected within 1 month after birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have documented spread of OvHV-2 from sheep to bison over distances of up to 5 km [49]. The infection with OvHV-2 predominantly occurs during the perinatal period [6]. Incubation periods after experimental inoculation of cattle are 2-12 weeks [80].…”
Section: Transmission and Incidencementioning
confidence: 99%
“…MCF is characterized by extensive pathological changes with little evidence of viral antigen in affected organs, although viral DNA can be detected by in situ hybridisation or PCR [6,13]. Experimental infection of OvHV-2 and AlHV-1 in rabbits has given insights into the pathogenesis of the disease.…”
Section: Pathogenesismentioning
confidence: 99%